2022
DOI: 10.3389/fcimb.2021.789398
|View full text |Cite
|
Sign up to set email alerts
|

TNF-TNFR1 Signaling Enhances the Protection Against Neospora caninum Infection

Abstract: Neospora caninum is a protozoan associated with abortions in ruminants and neuromuscular disease in dogs. Classically, the immune response against apicomplexan parasites is characterized by the production of proinflammatory cytokines, such as IL-12, IFN-γ and TNF. TNF is mainly produced during the acute phases of the infections and binds to TNF receptor 1 (CD120a, p55, TNFR1) activating a variety of cells, hence playing an important role in the induction of the inflammatory process against diverse pathogens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Furthermore, downregulated miR-361-3p was predicted to regulate the expression of MAP3K8 through the TNF signaling pathway in our study, and MAP3K8 has been reported to promote angiogenesis and inhibit inflammation with the participation of the tumor necrosis factor-α (TNF-α) signaling pathway [ 64 ]. Interestingly, C57BL/6 mice infected with N. caninum exhibited higher mortality associated with inflammatory lesions and increased parasite burden in the brain through TNF-TNFR1 signaling [ 65 ]. In addition, in our study, downregulated miR-128-5p was predicted to activate MKNK2 through the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, downregulated miR-361-3p was predicted to regulate the expression of MAP3K8 through the TNF signaling pathway in our study, and MAP3K8 has been reported to promote angiogenesis and inhibit inflammation with the participation of the tumor necrosis factor-α (TNF-α) signaling pathway [ 64 ]. Interestingly, C57BL/6 mice infected with N. caninum exhibited higher mortality associated with inflammatory lesions and increased parasite burden in the brain through TNF-TNFR1 signaling [ 65 ]. In addition, in our study, downregulated miR-128-5p was predicted to activate MKNK2 through the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%